NEGOTIATING FEMINIST IDEOLOGY IN ASMA NADIA’S NOVEL ASSALAMUALAIKUM BEIJING (Negosiasi Ideologi Feminis dalam Novel Asma Nadia Assalamualaikum Beijing) - Rasiah, NFN; Bilu, La (Kantor Bahasa Provinsi Sulawesi Tenggara, 2023)
Feminis dan Islam sering dibenturkan sebagai ideologi yang berlawanan. Islam sebagai agama seringkali dipandang sebagai sumber munculnya praktik-praktik ketidakadilan terhadap perempuan. Akhir-akhir ini, ada upaya untuk menghidupkan kembali nilai-nilai Islam untuk memperkuat posisi perempuan, terutama bagi mereka yang lahir dan hidup dalam konteks budaya berbasis Islam. Artikel ini bertujuan untuk mengungkap upaya negosiasi ideologi feminis dalam novel Assalamualaikum Beijing karya Asma Nadia. Feminisme multikultural digunakan sebagai perspektif dalam mengkaji isu ideologi feminis dalam novel dengan asumsi bahwa perempuan tidak diciptakan dan dikonstruksi dengan cara yang sama tetapi bergantung pada latar belakang sosial budayanya. Hasil penelitian menunjukkan bahwa novel ini menekankan kemandirian perempuan dengan mendorong mereka melalui pendidikan dan karir untuk melepaskan diri dari masalah ekonomi dan sosial. Namun, kemandirian dan kesetaraan perempuan juga harus didukung oleh nilai-nilai agama (Islam). Tampaknya novel ini melawan stereotip yang menganggap atribut agama (Islam) yang melekat pada perempuan sebagai kurungan atau bentuk subordinasi, seperti hijab dan taaruf, namun atribut tersebut justru menjadi bentuk pembebasan dan otonomi perempuan. Feminism and Islam are often viewed as opposing ideologies. Islam as a religion is seen by feminists as the source of the emergence of fraudulent practices against women. However, in the present decade, feminists have developed their ideas dealing with cultural attributes, particularly about Islamic rule on women. There has been an effort to enliven Islamic values to strengthen the position of women, especially for those who were born and live in an Islamic-based culture. This article aims to reveal the negotiation of feminist ideology in Assalamualaikum Beijing novel written by Asma Nadia. Multicultural feminism is used as a perspective in examining how feminist ideology is negotiated in the novel. The assumption that women are not created and constructed in the same social and cultural circumstances, thereby having a different way to exist in society. The results show that the novel emphasizes women's independence by encouraging women's education and career to liberate themselves from economic and social shortcomings. However, women's independence and equality must also be in line with religious (Islamic) values. It seems that the novel fights against the stereotypes of Islamic attributes attached to women as confinement or a form of subordination, such as hijab and taaruf, these attributes, on the other hand, become a form of women's self-liberation and autonomy.